Evolution of erythrocyte morphology in amphibians (Amphibia: Anura) - Wei,Jie (2015)
ABSTRACT We compared the morphology of the erythrocytes of five anurans, two toad species - Bufo gargarizans (Cantor, 1842) and Duttaphrynus melanostictus (Schneider, 1799) and three frog species - Fejervarya limnocharis (Gravenhorst, 1829), Microhyla ornata (Duméril & Bibron, 1841), and Rana zhenhaiensis (Ye, Fei & Matsui, 1995). We then reconstructed the ancestral state of erythrocyte size (ES) and nuclear size (NS) in amphibians based on a molecular tree. Nine morphological traits of erythrocytes were all significantly different among the five species. The results of principal component analysis showed that the first component (49.1% of variance explained) had a high positive loading for erythrocyte length, nuclear length, NS and ratio of erythrocyte length/erythrocyte width; the second axis (28.5% of variance explained) mainly represented erythrocyte width and ES. Phylogenetic generalized least squares analysis showed that the relationship between NS and ES was not affected by phylogenetic relationships although there was a significant linear relationship between these two variables. These results suggested that (1) the nine morphological traits of erythrocytes in the five anuran species were species-specific; (2) in amphibians, larger erythrocytes generally had larger nuclei.